The Fruitcake Special and other Stories - Brennan F. Frank (Cambridge english readers Level 4)
Five stories about discovery - a perfume that attracts men, a book that shows peoples thoughts, a remarkable change in an old womans life, the secret of high intelligence, and a way of making time stand still - make up this entertaining collection.